CORONALOGY: Multidisciplinary Academic Analysis in Perspective of Covid-19 - Balkanlı, Ali Osman; Yazici, Ayşe Meriç; Levent, Cüneyd Ebrar; Darıcı, Sefer; Seydibeyoğlu, Elif Alyamaç; Şen, Erdal Ş; Bağcı, Erdem; Özyıldız, Figen; Peschke, Lutz; Seydibeyoğlu, M. Özgür; Salepçioğlu, Murat Adil; Çanakçıoğlu, Mustafa; et al. (Sciendo, 2020)
The book aims to contribute to the new paradigm of sense-able covid-19 from and analytical perspective of different disciplines, to define and relate that kinds of multi disciplines able to provide users with relation of contextual services, to relate and analyse their dynamics and to react accordingly, in a seamless exchange of information during pandemic terms. In this context the book's main aim is to understand the complexities of society's pandemic beginning from information that is theoretically accessible from various viewpoints, through a multidisciplinary approach and in multiple contexts, both indoors and outdoors. In addition, the book will be examined in COVID-19 and later changes and transformations. ABSTRACTING & INDEXING CORONALOGY: Multidisciplinary Academic Analysis in Perspective of Covid-19 is covered by the following services: EBSCO Discovery Service Google Scholar J-Gate Naviga (Softweco) Primo Central (ExLibris) ReadCube Summon (ProQuest) TDOne (TDNet)